Effect of ion-dipole interaction on the formation of polar extended-chain crystals in high pressure-crystallized poly(vinylidene fluoride). (5th December 2018) - Ren, Jia-Yi; Zhang, Guoqiang; Li, Yue; Lei, Jun; Zhu, Lei; Zhong, Gan-Ji; Li, Zhong-Ming
Abstract: The manipulation of crystal superstructure and polymorphism of poly(vinylidene fluoride) (PVDF) are of great technical importance to expand its applications in flexible electronics. In this work, strong ion-dipole interaction via the introduction of cetyltrimethylammonium bromide (CTAB) in PVDF induced zig-zag conformers [i.e., the precursor nuclei of β/γ folded chain crystals (FCCs)]. Meanwhile, favorable conditions (i.e., high temperature and high pressure) for the pseudohexagonal (hex) paraelectric (PE) phase with gauche conformers [i.e., the precursor nuclei of extended-chain crystals (ECCs)] are purposely chosen to study whether there is any synergy between the ion-dipole interaction and ECCs. It is interesting to find that the high pressure/high temperature hex PE phase can be substantially affected by the strong ion-dipole interaction between PVDF and CTAB. For the neat PVDF melt, most hexagonal folded-chain (h-FC) nuclei ultimately lead to major β/γ ECCs. For the PVDF melt with 5 wt% CTAB, the β/γ FC nuclei induced by the strong ion-dipole interaction compete with the h-FC nuclei at the initial nucleation stage. The β/γ FC nuclei are found to be more kinetically favorable in the beginning under a high pressure, leading to major β/γ FCCs and minor β/γ ECCs. Furthermore, compared to neat PVDF, addition of 5 wt% CTAB resulted in ECCs of a thinner lamellar thickness. Finally, this new understanding leads to a modified T-P phase diagram, in which the kinetically favorable area for α/β/γ FC nucleation expands to higher temperatures because of the strong ion-dipole interaction. Graphical abstract: Highlights: The β/γ FC nuclei induced by strong ion-dipole interaction are kinetically favorable at the initial nucleation stage. The strong ion-dipole interaction suppressed lamellar thickening resulting in thinner lamellar thickness of β/γ ECCs. A modified T-P phase diagram reveals the effect of ion-dipole interaction on the formation of polar extended-chain crystals.